2013
DOI: 10.3758/s13423-013-0438-8
|View full text |Cite
|
Sign up to set email alerts
|

Lost ability to automatize task performance in old age

Abstract: Can elderly adults automatize a new task? To address this question, 10 older adults each performed 10,080 training trials over 12 sessions on an easy but novel task. The psychological refractory period (PRP) procedure was then used to evaluate whether this highly practiced task, when presented as task 2 along with an unpracticed task 1, could proceed automatically. If automatic, task 2 processing should bypass the bottleneck and, therefore, not be delayed while central attention is devoted to task 1, yielding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 12 publications
6
29
1
Order By: Relevance
“…Some situations in which one or the other or both of the tasks are simple and very extensively practiced show indications in younger adults that the bottleneck can be completely bypassed (Maquestiaux et al, 2008;Ruthruff et al, 2006). Older adults failed to show these indications even after very extensive training (Maquestiaux, Laguë-Beauvais, Ruthruff, Hartley, & Bherer, 2010;Maquestiaux, Didierjean, Ruthruff, Chauvel, & Hartley, 2013). Older adults do show evidence of partial bypass when Task 2 stimuli and responses are ideomotor compatible (Hartley et al, 2015) or very strongly associated (Experiment 2, possibly), and the magnitude of the effect is the same as in younger adults (Hartley et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some situations in which one or the other or both of the tasks are simple and very extensively practiced show indications in younger adults that the bottleneck can be completely bypassed (Maquestiaux et al, 2008;Ruthruff et al, 2006). Older adults failed to show these indications even after very extensive training (Maquestiaux, Laguë-Beauvais, Ruthruff, Hartley, & Bherer, 2010;Maquestiaux, Didierjean, Ruthruff, Chauvel, & Hartley, 2013). Older adults do show evidence of partial bypass when Task 2 stimuli and responses are ideomotor compatible (Hartley et al, 2015) or very strongly associated (Experiment 2, possibly), and the magnitude of the effect is the same as in younger adults (Hartley et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, studies in the wider literature on aging and dual tasking using the psychological refractory period (PRP) effect have found that, while older adults still exhibit a dual task cost following substantial training (Maquestiaux, Didierjean, Ruthruff, Chauvel, & Hartley, 2013), there are certain task responses that may remain almost entirely automatic with age. These largely involve well-learned responses such as word recognition (Lien et al, 2006) and ideomotor responses (where the sensory feedback produced by the response is related to the stimulus, Hartley, Seaman, & Maquestiaux, 2015).…”
Section: Limitations and Prospects For Future Researchmentioning
confidence: 99%
“…As a consequence, practice-related task automatization is a promising mechanism to explain the elimination of dual-task interference with practice. A series of studies (e.g., Maquestiaux, Didierjean, Ruthruff, Chauvel, & Hartley, 2013; Maquestiaux, Laguë-Beauvais, Ruthruff, & Bherer, 2008; Maquestiaux, Laguë-Beauvais, Ruthruff, Hartley, & Bherer, 2010; Ruthruff et al, 2006) tested the ability of task automatization by providing extensive single-task practice with an auditory-verbal task (e.g., low and high pitched tones were mapped on verbal low and high responses, respectively) in single-task trials across multiple practice sessions. In a following test session, the practiced auditory-verbal task was combined with a new visual-manual task (e.g., the digits 1 , 2 , 3 , 4 or the letters A , B , C , D were mapped on manual finger responses) in a PRP dual-task situation.…”
Section: Mechanisms Of Practice-related Optimization Of Dual-task Permentioning
confidence: 99%